Credit default swaps and bank loan sales: evidence from bank syndicated lending - Iftekhar Hasan; Deming Wu (Bank of Finland, 2016)
Do banks use credit default swap hedging to substitute for loan sales? By tracking banks' lending exposures and CDS positions on individual firms, we find that banks use CDS hedging to complement rather than to substitute for loan sales. Consequently, bank loan sales are higher for firms that are actively traded in the CDS market. In addition, we find evidence that suggests that banks sell CDS protection as credit enhancements to facilitate loan sales. This study employs identification strategies similar to the "twin study" design to separate the effects of borrower-side and lender-side factors, and to minimize the omitted-variables bias.
URN:NBN:fi:bof-201604291111
Keywords: G14; G21; G23; G28; G32; 330